PENGARUH QUANTUM TEACHING TERHADAP HASIL BELAJAR GAMBAR TEKNIK SISWA XII IPA SMA - Solfi Ayuna Putri; Yahya .; Yusron Wikarya (Serupa The Journal of Art Education, 2012)
Abstract The purpose of this research is to see the effect of Quantum Teaching model forward the result of student  picture technique SMA Negeri 1 Gunung Talang. The kind of the research is quasi experiment with the design two group post-test only design. The population of the research is all of the student XII IPA SMA Negeri 1Gunung Talang. The sample of the research is taken with random technique. In this research as experimental class XII IPA 2 and as control class is XII IPA 1. The learning outcomes is sees in the form of cognitive learning outcomes. The average of the student’s learning outcome in experimental class are higher than the control class. After obtained T-Test,the researcher get Tcalculate = 2,878 and Ttable = 2,002 (tcalculate>ttable). Kata kunci: Quantum Teching, Eksperimen, kontrol, gambar teknik.